Desmoplakin missense and non-missense mutations in arrhythmogenic right ventricular cardiomyopathy: Genotype-phenotype correlation. (15th December 2017) - Castelletti, Silvia; Vischer, Annina S.; Syrris, Petros; Crotti, Lia; Spazzolini, Carla; Ghidoni, Alice; Parati, Gianfranco; Jenkins, Sharon; Kotta, Maria-Christina; McKenna, William J.; Schwartz, Peter J.; Pantazis, Antonis
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is traditionally considered as primarily affecting the right ventricle. Mutations in genes encoding desmosomal proteins account for 40–60% of cases. Genotype-phenotype correlations are scant and mostly non gene-specific. Accordingly, we assessed the genotype-phenotype correlation for desmoplakin ( DSP ) missense and non-missense mutations causing ARVC. Methods and results: We analyzed 27 ARVC patients carrying a missense or a non-missense DSP mutation, with complete clinical assessment. The two groups were compared for clinical parameters, basic demographics such as sex, age at diagnosis, age at disease onset, as well as prevalence of symptoms and arrhythmic events. Missense DSP variants were present in 10 patients and non-missense in 17. Mean age at diagnosis and at first arrhythmic event did not differ between the two groups. Also the prevalence of symptoms, either major (60% vs 59%, p = 1) or all (80% vs 88%, p = 0.61), did not differ. By contrast, left ventricular (LV) dysfunction was significantly more prevalent among patients with non-missense mutations (76.5% vs 10%, p = 0.001), who were also much more likely to have a structural LV involvement by Cardiac Magnetic Resonance (CMR) (92% vs 22%, p = 0.001). Conclusions: For ARVC patients, both missense and non-missense DSP mutations carry a high arrhythmic risk. Non-missense mutations are specifically associated with left-dominant forms. The presence of DSP non-missense mutations should alert to the likely development of LV dysfunction. These findings highlight the clinical relevance of genetic testing even after the clinical diagnosis of ARVC and the growing clinical impact of genetics.